Operations, Logistics and Supply Chain During and Post-Covid-19: Challenges, Lessons and Way Forward; Case Study of Sultanate of Oman (Journal of Finance, Business and Management Studies, 2022)
The unprecedented coronavirus pandemic has exposed many industries leading to massive losses of property and lives. In order to prevent the spread of the virus and more loss of life, governments across the globe have enforced some restrictions. This has also been the case in Oman where these restrictions have unfortunately impacted movement of people and activities across different industries including supply chain, logistics and operations adversely. This research paper assesses the challenges that the virus has brought to these three industries, lessons and provides recommendations on the way forward. Given the current problems in the supply chain, the recommendations provided by this study will be useful to properly manage the industry and come out strong.
Keywords: COVID-19; Supply chain; Disruption; Risk management